Adobe; build it yourself - McHenry, Paul Graham (Tucson : University of Arizona Press, 1973)
The purpose of this book is to enable you to intelligently and realistically plan and build your own home. Primary emphasis is placed on adobe construction, but as you will find in pursuing the project, there are many other materials and problems with which you must deal, and many principles are discussed at length which would apply to building a home from many materials.
Introduction -- 1. History of Adobe -- 2. Planning your home -- 3. Space and room considerations -- 4. Financing ,permits, and insurance -- 5. Plans, setting grades, and staking -- 6. Foundations, concrete, and slabs -- 7. Adobe walls -- 8. Doors and frames, hardware, and windows -- 9. Roof beams, decking, and insulation -- 10. Floors -- 11. Plumbing -- 12. Heating and cooling -- 13. The electrical system -- 14. Roofing -- 15. Plastering, drywall, and ceramic tile -- 16. Cabinets and countertops -- 17. Paints and stains -- 18. Fireplaces -- 19. Landscaping and yard planning -- 20. Estimating and tools -- 21. Restoring old adobes -- 22. Conclusion -- Bibliography -- Index.
Includes bibliographical references and index.
Keywords: ADOBE HOUSES